Closed removable thread vascular anastomosis stent (Lasheen Vascular Stent) - Ahmed E Lasheen (Journal of Surgery and Surgical Research - Peertechz Publications, 2019)
Background: Vascular anastomosis is a most common and important part of many reconstructive transplant procedures. Venous anastomosis can be done by using coupling devices. In arterial anastomosis still the suture method is the main method, which is time consuming, need much experience, and associated by many complications specially with small arteries (microanastomosis). This study offers new type of stent (Lasheen vascular stent) for vascular anastomosis.